(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Electron beam accelerators are used in many applications, such as basic physical research, chemistry, medicine, molecular biology, microelectronics, agriculture and industry, among others. The majority of the accelerators have electrons from a hot tungsten filament and their energy is increased as it passes through an electric field in the vacuum chamber. For industrial purposes, the most common model is Dynamitron®. At IPEN-CNEN/SP, there is an electron beam accelerator Dynamitron® Type (Manufactured by RDI - Radiation Dynamics Inc., 1978) model DC1500/25/4. The technology applied was available in the 60´s and 70´s, but, nowadays is obsolete. Moreover, there are not original spare parts for this equipment any longer. The aim of this work is to develop a nationalized automated operation system for the accelerator, to replace the old equipment. electron beam, accelerator, automated system, Dynamitron®